An Analysis of Code Switching in Teaching English Process at SMK N 2 Kubu - Arisuta, Pande Gede Darma; Ramendra, Dewa Putu; Utami, I G A Lokita Purnamika (English Education Department STKIP Agama Hindu Singaraja, 2024)
This study focused on examining the various types and functions of code-switching employed by the teacher in the context of teaching English as a foreign language at SMK N 2 Kubu. This research is a descriptive qualitative study. The subject of this study is an English teacher who teaches 10th-grade students. Data were gathered through observation. The tools utilised in this study include observation sheets, video recorders, and a tape recorder. The findings indicated that English teachers employ three distinct types of code-switching. The categories include intra-sentential code-switching at 56%, inter-sentential code-switching at 24%, and tag code-switching at 20%. Teachers utilise three functions of code-switching: topic switch (6%), affective function (16%), and repetitive function (78%).